Monitoring Arthropods in maize and pasture fields in São Miguel and São Jorge Islands: IPM-Popillia Project - Teixeira, Mário (2023)
ABSTRACT: The dataset presented here is an achievement of the H2020 European project "Integrated Pest Management of the Invasive Japanese Beetle, Popillia japonica (IPM-Popillia)". This project addresses the challenge of a new risk to plant health in Europe, the invasion of the Japanese beetle, Popillia japonica (Newman, 1838) (Coleoptera, Rutelidae) and provides an environmentally friendly IPM Toolbox to control the expanding pest populations across Europe. This study aims to present the records of terrestrial arthropod diversity with a special focus on four groups belonging to Carabids and Staphylinid beetles (Coleoptera), Opiliones and Anisolabididae (Dermaptera), collected with the potential to be used as biocontrol agents against P. japonica in future Integrated Pest Management programmes. A thorough sampling programme was conducted in maize and pasture fields in two Islands of the Azores (São Miguel and São Jorge) in the summer of 2022.